Entre a justiça e a injustiça ambiental: atuação do poder judiciário nos conflitos ambientais. - Castilho, Adriana Guedes de (2013)
The research analyzed the performance of the Judiciary Power through the exam of the current judicial decisions of public civil action proposed by the Federal Public prosecution of the of Paraíba and Amazon before an environmental damage. The focus of it analyzes is the human and environmental relationship with emphasis in the environmental subject not just in preservation terms, but distribution and justice. For so much, the research dove in the new universe of the political ecology and of the movement for environmental justice that you relate environmental problems and social inequalities as originated of a model of unjust development, where the negative environmental damages relapse, in his majority, for the poorest populations and discriminated. This environmental focus differs of the traditional ecological studies about shortage and preservation of natural resources, there be to analyze the environment and the social actors jointly. He took place, in the first chapter, a literature revision on the environment and the environmental damage, the origin of the movement for environmental justice, through authors of the field of the right, environmental sociology, political ecology and ecological economy, and later the relationship of the movement with the development of a nation. In a second moment, it was studied the environmental conflicts as form of environmental injustice, through the approach of the social sciences, being outstanding the concept, the types of conflicts, the currents that look for solutions for the conflicts and the methodological bases in political ecology for the environmental conflicts. In the third chapter the research was accomplished, through the analysis of public civil actions environmental proposed by the Public prosecution service of the state of Paraíba and Amazon, being the results distributed in tables and graphs that indicate that the state in the state of Paraíba there are still few environmental actions when compared with Amazon; that the more predominant environmental conflict is the space that it elapses of the human action; the larger time of the conflicts is the ones that elapse of territorial disputes and the ones that involve great enterprises; the request of the Public prosecution service and the judicial decision tend her an obligation of to do or not to do to repair the damage environmental with condemnation in money and the Judiciary Power of the state of Amazon related environmental degradation and risks to the human beings in most of their actions, taking communion with the premises of the movement for environmental justice and political ecology that analyze the environment and populations for the consequences.